Long-term QT prolongation in monkeys after doxorubicin administration at doses similar to breast cancer therapy - Bodziock, George M.; Meléndez, Giselle C. (Frontiers in Cardiovascular Medicine, 2023)
Background Studies in small animals and human patients have suggested that anthracyclines may prolong cardiac repolarization, or at least inhibit repolarization reserve, predisposing to QT prolongation and dangerous arrhythmias such as Torsades de pointes. This association in humans is difficult to confirm due to multiple confounding variables such as the presence of other medications and concurrent illness. Objectives Identify a long-term association between anthracycline administration and repolarization prolongation in nonhuman primates, which can be measured as prolonged QT/QTc intervals on surface electrocardiogram. Methods Five female African Green monkeys (AGMs) aged 13 ± 1 years received Doxorubicin (Dox) at doses similar to women treated for breast cancer (30–60 mg/m2/biweekly IV, total cumulative dose: 240 mg/m2) and underwent 12-lead electrocardiogram (ECG) before and 15 weeks after the final dose of Dox treatment. A blinded paired analysis was performed on ECG derived heart rate (HR), QRS, QT and QT corrected for HR (QTc) interval durations. Results After Dox, all monkeys exhibited increased QT (BL: 323.2 ± 27.4 ms vs. Post-Dox: 366.4 ± 18.7 ms, p = 0.002) and QTc (BL: 440.2 ± 22.8 ms vs. Post-Dox: 500.8 ± 22.0 ms, p = 0.009) intervals, without any significant changes in HR or QRS duration (p = 0.92 and p = 0.47 respectively). Conclusions AGMs treated with Dox exhibited long-term QT and QTc prolongation, along with the expected cardiotoxicity (LVEF decrease). While similar findings were shown in small animal studies, confounders make human association difficult to prove. Our finding provides a valuable intermediary step, showing direct effect of Dox on repolarization in nonhuman primates.